Accidental penetration of screw driver in the cranial cavity. - Al-Shalchy, Ali K.; Saeed, Mohammed (Journal of the Faculty of Medicine Baghdad, 2010)
Background: penetrating foreign body is a common problem but penetration by screw driver is very uncommon Patient & method: A nine years old boy presented with penetrating screw driver through the medial canthus of the eye. Result: the foreign body removed under GA with good result. Conclusion: minimal invasive procedure are preferred when we have penetrating head injury.